Speech Development of Preschool Children Who Stutter as A Pedagogical Problem - Salamova Feruza Khakimbekovna; Alhiyasova Juldyz Dinmuhammedovna (Euro Asian Journal Publishing, 2024)
This article discusses the problem of stuttering in preschool children. The author considers this problem as an aspect that slows down the process of the overall development of the child’s personality and his social adaptation. Describes the causes of stuttering in children and effective methods for eliminating it.
Keywords: preschool age; stuttering; problem; speech formation